Remote Sensing: An environmentally friendly tool to enhance environmental education at the Department of Remote Sensing, Universiti Teknologi Malaysia - Kanniah, Kasturi; Hashim, Mazlan; Seeni Mohd., Mohd. Ibrahim (2001)
Environmental education (EE) is a learning process that develops people's knowledge, awareness and understanding about the environment, investigates about environmental problems and develops critical thinking, problem solving and effective decision making skills related to particular environmental problems. Integrating remote sensing (RS) technology into environment is a new way to promote EE where RS is being used as a tool to explore environmental problems and find quick and best solution to the problems.